Deconstructing dams and disease: predictions for salmon disease risk following Klamath River dam removals - Bartholomew, Jerri L.; Alexander, Julie D.; Alvarez, Justin; Atkinson, Stephen D.; Belchik, Michael; Bjork, Sarah J.; Foott, J. Scott; Gonyaw, Alex; Hereford, Mark E.; Holt, Richard A.; McCovey, Barry; Som, Nicholas A.; et al. (Frontiers in Ecology and Evolution, 2023)
The health of fish populations and the river systems they inhabit have broad ecological, cultural, recreational, and economic relevance. This is exemplified by the iconic anadromous salmonid fishes native to the West Coast of North America. Salmon populations have been constrained since the mid nineteenth century by dam construction and water reallocation. In the Klamath River (Oregon and California, USA), a series of dams built in the early-mid 20th century cut the basin in two and blocked anadromous fish access to more than 600 river kilometers. This dramatic loss of habitat, coupled with infectious diseases and resulting epizootics, have impacted the wellbeing of these salmonid populations. In 2023-2024, the Klamath River will undergo the largest river restoration project in US history. Removal of the four lowermost dams will cause profound physical changes to the river, including flow, water temperature, and channel geomorphology. The dam removals will reconnect the lower and upper portions of the basin, and provide fish passage after a century of segregation. Reestablishment of upstream and downstream fish movements will also alter the occupancy and abundance of the salmonid hosts and their pathogens. The increased habitat availability and longer migration routes will increase duration of pathogen exposure and potential impacts on juvenile survival and adult pre-spawn mortality. However, restoration of more natural flow and sediment regimes will decrease overall fish disease risk by disrupting complex parasite life cycles. To better understand these multifarious, competing factors, we review the salmonid species in the Klamath River, and provide an overview of their historical pathogen challenges and associated diseases and use this as a framework to predict the effects of dam removals on disease dynamics. Our review and predictions are a synthesis of expertise from tribal biologists, fish health specialists and fish biologists, many of whom have lived and worked on the Klamath River for decades. We conclude with recommendations for expansion of current pathogen monitoring and research efforts to measure changes in host-pathogen dynamics basin-wide.